(untitled) (Journal of Philosophy Culture and Political Science, 2020)
Social cognition is the way in which people process, remember, and use information in social contexts to explain and predict their own behavior and that of others. Children’s social cognition may be influenced by multiple factors, both external and internal to the child. In the current study, two aspects of social cognition were examined: Theory of Mind and Emotion Understanding. A person is considered as a system of integral qualities: natural and social, rational and irrational, emotional and physical, conscious and unconscious. Focusing on the integral properties of the personality allows us to more holistically and comprehensively consider its essence as the unity of three components: biological, psychological and social. The methodological basis of the study of personality socialization are: the vitalist concept, which puts in the first place the subjective quality of the individual in the individual and social plan; a universal paradigm that focuses on the spiritual component of a person, based on the biopsychosocial essence of the person. Based on a critical understanding of the provisions of the vitalist and universal concept, the following interpretation of personality socialization is distinguished. This article describes the newly emerging field of implicit social cognition from preschool through elementary school. A special emphasis is placed on discoveries concerning young children’s thinking and understanding of themselves and their social groups in the domains of gender and race. Key words: socialization, social cognition, theory of mind, emotion understanding, social roles, personality, social group, modeling of adult’s life, game, emotional and volitional sphere, communicative competence.